Students’ Perceptions on Translanguaging in English Teaching-Learning Process - Andi Nur Hafidzah Aliyah Qashas; Nurdin Noni; Chairil Anwar Korompot (Journal of Excellence in English Language Education, 2023)
This study aims to determine students' perceptions of class 2020 of the English Education Study Program of Universitas Negeri Makassar about the use of translanguaging in the English teaching-learning process. The researcher used a mixed-method research design (quantitative-qualitative), using a questionnaire and interview to collect the data. The sample questionnaire is 165 participants taken by voluntary sampling technique and five participants for the interview taken by purposive sampling technique. The data analysis from the questionnaire revealed that the student had positive perceptions about the lecturer's use of translanguaging, as evidenced by a mean score of 36.41 and classified as positive because it helped them to have a better understanding and participated better and more efficiently in the lesson, and the student has moderate perceptions about their own translanguaging practices, as evidenced by a mean score of 17.27 and classified as moderate. The questionnaire result indicated that students have moderate to positive attitudes overall. The result of the interview showed that five students responded positively to the practice of translanguaging. Based on the interview result, the student perceived that when translanguaging occurred in the classroom, the English teaching-learning process was efficient because most students understood the material given better, participated actively, and were motivated to improve their English skills.